Emerging Postharvest Treatment of Fruits and Vegetables - Barman, Kalyan; Sharma, Swati; Siddiqui, Mohammed Wasim; Apple Academic Press (Toronto ; New Jersey : Apple Academic Press, 2018)
With the increasing need and demand for fresh fruits and vegetables, the field of postharvest science is continuously evolving. Endeavors are being made by scientists involved in postharvest research for maintenance of the quality and safety of fresh horticultural produce to enhance the postharvest life and to extend the availability of the produce in both time and space. This volume, Emerging Postharvest Treatment of Fruits and Vegetables, addresses the demand for the development and application of effective technologies for preservation of perishable food products, particularly fresh fruits and vegetables. It provides an abundance of up-to-date information about postharvest treatments. The chapters discuss a number of innovative technologies to prolong and enhance postharvest fruits and vegetables. This book will be valuable for those concerned with horticulture and postharvest technology. It provides essential information for students, teachers, professors, scientists, and entrepreneurs engaged in fresh horticultural produce handling related to this field.
Postharvest Treatments to Alleviate Chilling Injury in Fruits and Vegetables----Kalyan Barman, Swati Sharma, and Ram Asrey -- Heat Treatments for Enhancing Storability of Fruits and Vegetables----Susan Lurie -- Calcium: An Indispensable Element Affecting Postharvest Life of Fruits and Vegetables----T. Vijay Yadav and B. V. C. Mahajan -- Effects of Methyl Jasmonate Treatment on Fruit Quality Properties----Mara Serrano, Alejandra Martnez-Espl, Pedro J. Zapata, Salvador Castillo, Domingo Martnez-Romero, Fabin Guilln, Juan M. Valverde, and Daniel Valero -- Nitric Oxide for Enhancing Storage Life of Fruits and Vegetables----Shuhua Zhu, Lili Zhang, Changbao Chen, and Jie Zhou -- Nanotechnology in Packaging of Fresh Fruits and Vegetables----Ovais Shafiq Qadri, Kaiser Younis, Gaurav Srivastava, and Abhaya Kumar Srivastava -- Biological Control of Postharvest Diseases----R. R. Sharma and S. Vijay Rakesh Reddy -- Application of Ozone as a Postharvest Treatment----Serdar ztekin -- Advances in Edible Coatings and Films for Fresh Fruits and Vegetables----Evening Stone Marboh and Alok Kumar Gupta -- Postharvest Treatments to Reduce Browning in Minimally Processed Products----Alemwati Pongener, M. B. Darshan, and Aabon W. Yanthan -- Essential Oils and Plant Extracts as Natural Antimicrobial Agents----A. Garca Heredia, J. E. Dvila-Avia, C. Zoellner, L. E. Garcia-Amezquita, N. Heredia, and S. Garca -- Polyamines for Preserving Postharvest Quality----Swati Sharma, Anil Kumar Singh, Sanjay Kumar Singh, Kalyan Barman, Sunil Kumar, and Vishal Nath.
Includes bibliographical references and index.
Also available in print format.
Keywords: TECHNOLOGY & ENGINEERING / Food Science; Electronic books